Ultra trace simultaneous determination of 50 polycyclic aromatic hydrocarbons in biota using pMRM GC-MS/MS. Issue 1 (2nd January 2020) - Kwok, Honoria; Yan, Jeffrey; Brunswick, Pamela; McMaster, Mark; Evans, Marlene; Kim, Marcus; Helbing, Caren; van Aggelen, Graham; Shang, Dayue
Abstract: A saponification extraction method with gas chromatography pseudo-MRM (pMRM) mass spectrometry detection was developed for the determination of 50 total polycyclic aromatic hydrocarbons (TPAH50, a combination of parent and alkylated homologues) in biota. The method was aimed at monitoring and identification of potential TPAH contaminants in bitumen impacted environments. Alkylated PAHs were determined by multi-level, quantitative calibration using parent PAHs. The developed and thoroughly validated method required only one injection for TPAH50 analysis which represents significant saving of time and expensive authentic alkylated standards. The current method was tested with certified reference mussel tissue NIST 1974c and performed well. In a comparison study, the method reached a limit of quantitation (LOQ) for the TPAH50 between 0.1 and 0.2 ng g −1, while the QuEChERs enhanced matrix removal – lipid (EMR) kit produced by Agilent showed an LOQ of 5–10 ng g −1 . The current method relied on response factors (RF) for the quantitation of alkylated PAHs determined against parent PAHs. These RFs were shown to be stable and consistent over the course of 1 year, during which over 200 routine environmental biota monitoring samples were analyzed. The environmental biota monitoring samples analyzed include muscle, carcass and liver, with an average total PAH50 concentration of 13, 90 and 135 ng g −1, respectively. Results show significant differences in the distributions of 1 ringed, 2 ringed, 3 ringed, 4 ringed, and 5+ ringed TPAHs between the types of biota samples.